2020
DOI: 10.1101/2020.05.14.096354
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Stress-induced translation inhibition through rapid displacement of scanning initiation factors

Abstract: Running title: Stress-induced changes in the RNA-bound proteome Highlights:A quantitative proteomic approach reveals rapid stress-induced changes in RNA-binding Translation shutdown is driven by loss of mRNA binding by scanning initiation factors eIF4B and Ded1 have key but separate roles in driving the stress response Heat shock invokes rapid RNA degradation by Xrn1, selective for translation machinery 2 SUMMARY Cellular responses to environmental stress are frequently mediated by RNA-binding proteins (RBPs).… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(46 citation statements)
references
References 78 publications
2
44
0
Order By: Relevance
“…S4C). We compared the CRAC reads to poly(A)-enriched RNA-seq from the background (untagged) yeast strain grown in matched conditions (Bresson 2020), which were also reproducible ( Fig S4D). Counting reads on full-length transcripts, and normalising by transcript length and total density to transcripts per million (TPM) (Wagner, Kin, and Lynch 2012), revealed a clear enrichment for a small proportion of mRNAs ( Fig 4C).…”
Section: Ssd1 Associates Primarily With 5ʹutrs Of Mrnas Encoding Cellmentioning
confidence: 94%
See 1 more Smart Citation
“…S4C). We compared the CRAC reads to poly(A)-enriched RNA-seq from the background (untagged) yeast strain grown in matched conditions (Bresson 2020), which were also reproducible ( Fig S4D). Counting reads on full-length transcripts, and normalising by transcript length and total density to transcripts per million (TPM) (Wagner, Kin, and Lynch 2012), revealed a clear enrichment for a small proportion of mRNAs ( Fig 4C).…”
Section: Ssd1 Associates Primarily With 5ʹutrs Of Mrnas Encoding Cellmentioning
confidence: 94%
“…CRAC studies were done in biological duplicates on cells growing exponentially in synthetic medium at 30°C, and following heat shock at 42°C for 16 minutes, a condition in which total Ssd1 binding to RNA markedly increases (Bresson 2020). Expression of tagged constructs was verified by western blot (Fig.…”
Section: Ssd1 Associates Primarily With 5ʹutrs Of Mrnas Encoding Cellmentioning
confidence: 99%
“…Using pcDNA5-FRT/TO as a starting point, we generated two additional parental vectors with pre-inserted tandem-affinity purification tags, either an N-terminal, FH-tag (FLAG-Ala4-His8) or Cterminal HF-tag (His8-Ala4-FLAG) ( Figure 2A). We have recently shown that these tags work well for tandem affinity purification, including in the denaturing conditions used for CRAC (Bresson et al, 2020).…”
Section: Design and Cloning Of Viral Expression Constructsmentioning
confidence: 99%
“…Approximately 30 μg of protein was resolved on a 4-20% Miniprotean TGX gel, run in Tris-Glycine running buffer at 100 V. Subsequently, the gel was rinsed with water, stained for 1 hour with Imperial Protein Stain (Thermo Scientific), rinsed several times, and destained in water for three hours. Each lane was cut into four fractions and processed using in-gel digestion and the STAGE tip method, as previously described (Bresson et al, 2020;Rappsilber et al, 2007).…”
Section: Mass Spectrometrymentioning
confidence: 99%
See 1 more Smart Citation